SMURFS : THE LOST VILLAGE : Movie Novelization - Deutsch, Stacia; Peyo (New York : Simon Spotlight, 2017)
DVENTURE STORIES (CHILDREN'S / TEENAGE). The Smurfs go on an all-new adventure in this action-packed retelling of Sony Picture s Animation s film, Smurfs: The Lost Village! Smurfs: The Lost Village is an all-new, fully computer animated movie starring the voices of Demi Lovato as Smurfette, Rainn Wilson as Gargamel, Mandy Patinkin as Papa Smurf, Jack McBrayer as Clumsy, Danny Pudi as Brainy, and Joe Manganiello as Hefty that hits theaters April 7, 2017! It seems to Smurfette that everyone else in the Village has a purpose Papa Smurf leads, Baker Smurf bakes, and Grouchy grouches except for her. So what s the only girl Smurf in the village to do? Go in search of her purpose, of course! When she accidentally crosses paths with a mysterious creature that takes off into the Forbidden Forest, she follows, and the adventure begins! Smurfette is joined by Hefty, Brainy, and Clumsy, and together they form Team Smurf. Ages 9+
Keywords: Smurfs (Fictitious characters) -- Juvenile fiction; Film novelizations -- Juvenile fiction; Children's stories, English; Novelizations; Fiction; Juvenile fiction